Adapting to Climate Change Through Education : Promoting Sustainable Lifestyles in Schools - Makikui, Jefta Johannes; Hakim, Abdul; Parmawati, Rita; Rozuli, Ahmad Imron (Jurnal Pembangunan dan Alam Lestari, 2025)
The urgent and growing threat of climate change affects all aspects of human life in all sectors including the education sector. Schools are not only places to gain knowledge, but also agents of change towards a sustainable future. This research examines experiential learning and community engagement in promoting sustainable lifestyles in the context of Sekolah Penggerak in Manado City. This research uses a quantitative approach, evaluating the relationships between these variables and their impact in promoting sustainable lifestyles in the school environment using survey data collection techniques by distributing questionnaires and using regression data analysis techniques. The study's findings provide exciting proof which shows students' sustainable behavior is significantly impacted when experiential learning and community engagement are incorporated into the curriculum. A thorough plan that incorporates each of these elements has been successful in encouraging sustainable lives at Sekolah Penggerak Kota Manado. Put another way, a comprehensive strategy that integrates the idea of sustainability to practical school activities might help children develop good habits and beliefs. These findings have significant ramifications for the advancement of sustainable education, especially in relation to developing effective approaches to learning and producing environmentally conscious future generations. Keywords: Climate change adaptation, Education for Sustainability, Sustainable Lifestyle.